1968
DOI: 10.1099/00221287-54-3-319
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of NaCl Concentration of the Medium on the Potassium Content of Aerobacter aerogenes and on the Inter-relationships between Potassium, Magnesium and Ribonucleic Acid in the Growing Bacteria

Abstract: SUMMARYIrrespective of the nature of the growth-limiting substance, the potassium content of Aerobacter aerogenes (growing in a chemostat at a fixed dilution rate) increased progressively from about 1.3 % to 4-2 yo of the bacterial dry weight with changes in culture NaCl concentration from o to 40 g./l. Similarly, the potassium content of glycerol-limited A. aerogenes organisms, growing in a low ionic strength medium, varied with growth rate (from 0.9 % to 1.6 yo of the bacterial dry weight with changes in dil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

1970
1970
1994
1994

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…(These calculations assume that cytoplasmic MOPS is 70% anionic [11].) The amounts of Mg2+ and nucleic acid, the other major ionic species in the cytoplasm, also do not appear to vary with external osmolarity (12,23,49). The invariance of the excess cationic charge of osmotically regulated cytoplasmic solutes with accumulation of osmoprotectants argues against a variation in the cytoplasmic amounts of inorganic ions other than K+.…”
Section: Discussionmentioning
confidence: 99%
“…(These calculations assume that cytoplasmic MOPS is 70% anionic [11].) The amounts of Mg2+ and nucleic acid, the other major ionic species in the cytoplasm, also do not appear to vary with external osmolarity (12,23,49). The invariance of the excess cationic charge of osmotically regulated cytoplasmic solutes with accumulation of osmoprotectants argues against a variation in the cytoplasmic amounts of inorganic ions other than K+.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly high external K+ concentrations may slow down the K+ loss from damaged cells. The K+ ion pool concentration is related to the medium sodium chloride content (21). High external sodium chloride concentrations may therefore magnify the physiological consequences of K+ loss from the osmoregulatory pool.…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned adsorption experiments were made with organisms grown in Mg2+-limited culture only; but since the wall composition of organisms is known to vary with the chemical nature of the environment (Ellwood & Tempest, 1967;Tempest, Dicks & Ellwood, I 968), it was of interest to determine whether the affinity with which organisms bound Mg2+ at their surfaces also varied with changes in the nature of the growth limitation. In this connexion, Tempest & Meers (1968) reported that A. aerogenes had a lower tolerance for NaCl when its growth was limited by Mg2+ availability than when its growth was limited by the availability of any other essential nutrient. This suggested that sodium ions impeded Mg2+ assimilation, possibly by competing for adsorption sites on the bacterial surface.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary account of this work has been published (Meers & Tempest, 1969 Growth conditions. Organisms were grown in 0.5 1. chemostats (Herbert, Phipps & Tempest, 1965) in the simple salts media described by Tempest & Meers (1968) and by . The chemostat was operated at a dilution rate of 0.3 h.-l and at a temperature of 35"; the pH value was automatically maintained throughout at pH 7-0 f 0.05.…”
Section: Introductionmentioning
confidence: 99%